Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Menulis Teks Eksposisi Siswa Kelas VIII SP 2 Sungguminasa - Setiawati Setiawati; Aco Karumpa; Besse Syukroni (Departement of Mathematics Education, 2023)
This study aims to determine the effect of the Problem Based Learning learning model on class VIII students of SMP Negeri 2 Sungguminasa. This type of research is experimental research with the pre-experimental method, the design of this study is the one pretest posttest group, namely a type of research that only involves 1 class as a experimental class carried out without a comparison group. The sample in this study was class VIII students totaling 28 students. Based on the results of research and data analysis regarding this statistical comparison, comparisons with categories of learning outcomes and comparisons of completeness levels prove an increase in student learning outcomes in class VIII SMP Negeri 2 Sungguminasa can be seen from student learning outcomes through descriptive statistical analysis before using the Problem Based Learning learning model on average the average student score is still below the KKM, which is 54.6 and after using the Problem Based Learning learning model, the average student score increases above the KKM 76.3. It is known that the Posttest value is 76.3 more than the Prest value which is 54.6. Furthermore, based on the results of inferential statistical analysis using the t-test formula, it is known that the tcount obtained is 3.367 with a frequency df = 28-1 = 27, at a significant level of 0.05 or 5%, the ttable is 1.701. So tcount> ttable or HO is assessed and H1 is accepted. Based on these results it can be concluded that there is a significant increase in student learning outcomes. This means that the use of the Problem Based Learning learning model has an effect on the ability to write exposition texts in class VIII students of SMP Negeri 2 Sungguminasa.